1973
DOI: 10.1346/ccmn.1973.0210515
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of the Occurrence and Origin of Sedimentary Palygorskite-Sepiolite Deposits

Abstract: Abstract--Marine and non-marine palygorskite-sepiolite deposits are found throughout the world and occur interbedded with chert, dolomite, limestone, phosphates and other non-detrital sedimentary rocks. The origin of these high-magnesium clays has long been attributed to either alteration of volcanic ash or the structural transformation of smectite clays. More recently, others have argued origin by direct crystallization (neo-formation). Recent laboratory studies support this latter concept, particularly in en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0
3

Year Published

1979
1979
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(37 citation statements)
references
References 32 publications
1
33
0
3
Order By: Relevance
“…Palygorskite is found with chert, dolomite, limestone and other non-detrital sedimentary rocks (Isphording 1973). It weathers to smectite when mean annual rainfall is greater than 300mm (Paquet & Millot 1972).…”
Section: Borehole Coresmentioning
confidence: 99%
“…Palygorskite is found with chert, dolomite, limestone and other non-detrital sedimentary rocks (Isphording 1973). It weathers to smectite when mean annual rainfall is greater than 300mm (Paquet & Millot 1972).…”
Section: Borehole Coresmentioning
confidence: 99%
“…This would indicate that the presence of alumina in the mixture inhibits the formation of sepiolite from solution. Millot (1960), Isphording (1973, and Heron and Johnson (1966) have proposed an authigenic origin by direct precipitation for sepiolite in the natural sediments that they have studied. Precipitation could occur where the pH and MgO contents were high but A12O3 was low or absent.…”
Section: Previous Work On Sepiolitementioning
confidence: 99%
“…Palygorskite and sepiolite are formed mainly in marginalmarine and lacustrine, chemically restricted environments in arid and semiarid regions (Millot, 1970;Wiersma, 1970;Isphording, 1973;Weaver and Beck, 1977;Chamley et al, 1981;Singer and Galan, 1984). Previous research on the marine Pliocene and Quaternary of the Mediterranean has shown that palygorskite is best considered to be reworked from Paleogene North African sediments (Chamley and Millot, 1975;Chamley, 1975a andb, 1976;Chamley et al, 1977).…”
Section: Provenance and Climatic Significance Of The Clay Mineralsmentioning
confidence: 99%